The Effectiveness of Edotok (Education Media Video TikTok) To Prevent Unsafe Sex Among Adolescents - Fanesa Rahmawati; Meilani, Niken; Retnaningsih, Yuliantisari (International Conference on Health Sciences, 2026)
Promiscuous sexual behaviour among adolescents, especially high school students, has become a serious problem in Indonesia, including in Central Java. According to data from the Central Bureau of Statistics (BPS) in 2024, the number of free sex cases in Central Java ranked 3rd with 218 cases related to free sex among adolescents, including unwanted pregnancies (KTD), sexually transmitted infections (STI), and unsafe abortions. One effort to increase prevention and promote health education and attitude change is through effective education that aligns with the preferences of the younger generation. This study aims to produce educational media, namely TikTok videos, that can be used to increase prevention and promote better attitudes in high school adolescents about preventing promiscuous sex. The research method employed is a quasi-experimental study with a pretest-posttest control group design. The research sample comprised 80 high school students, divided into 2 groups: 40 in the experimental group (TikTok) and 40 in the control group (Slide). Analysis of data that is not normally distributed using the Wilcoxon and Mann-Whitney. The results indicate there was no significant difference in baseline attitude between the two groups (p=0.110). After the intervention, both groups experienced significant improvements in attitude (p<0.05); however, the video group showed a greater mean improvement than the slide group (60.50 vs 20.50). Mann-Whitney test results showed significant differences between groups (p=0.000). The conclusion of this research is that free sex prevention education using TikTok media has a greater effect on increasing prevention and directing to more positive things about free sex than education using Slide media.